2002
DOI: 10.1248/bpb.25.1436
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Anti-allergic Activities of Hydroxylamine and Related Compounds.

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used as analgesic or antipyretic agents for the clinical treatment of inflammatory diseases such as arthritis, lumbago and rheumatism. These NSAIDs (e.g., ibuprofen, aspirin, and indomethacin) exhibit an inhibitory action on the cyclooxygenase (COX) that catalyzes the biosynthesis of prostaglandins and thromboxane from arachidonic acid. There are two isoforms of the membrane-bound COXs, COX-1 expressed constitutively, and COX-2 induced by stimuli of cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…COX-2, the inducible form of the enzyme, can undergo rapid induction in response to many factors such as bacterial lipopolysaccharides, growth factors, cytokines and phorbol esters. 22,23) Therefore, in this paper, effect of 2-methoxycinnamaldehyde and 2-methoxycinnamic acid on COX activity, COX protein and COX mRNA expression in CECs with IL-1b inducement were also measured. For each of the primer sets, non-specific amplification was not visualized after electrophoresis and ethidium bromide staining of agarose gels.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2, the inducible form of the enzyme, can undergo rapid induction in response to many factors such as bacterial lipopolysaccharides, growth factors, cytokines and phorbol esters. 22,23) Therefore, in this paper, effect of 2-methoxycinnamaldehyde and 2-methoxycinnamic acid on COX activity, COX protein and COX mRNA expression in CECs with IL-1b inducement were also measured. For each of the primer sets, non-specific amplification was not visualized after electrophoresis and ethidium bromide staining of agarose gels.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they have been used as anti-skinning agents in paint, blocking agents in the polymer industry and chelators in variable industrial applications. Some oxime derivatives clinical used as anti-inflammatory and anti-allergic agents [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed the oximes have powerful antioxidants [8][9][10][11] antiepileptic drug [12], anti-inflammatory [13][14][15], antimicrobial [16,17], oxidative effect [18], antihyperglycemic agent [19] and hepatoprotective [20] activities.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for expecting such anti-inflammatory activity are as follows; 1) the stereochemistry at the chiral center (C3) was the same as that of D-alanine 2) the planarity between C4-C5 in naproxen might be replaced with the double bond nature of the amide function (N4-C5) 3) the zigzag structure in naproxen could be mimicked as the zigzag structure drawn in bold lines in Fig. 1 4) the planarity between C5-C6 in R-1 might be obtained by the π electron donation from the aromatic ring to the amide carbonyl function 5) R-1 had a naphthalene ring that might settle on the planar domain of the binding site of the COXs advocated by Gund et al 8 First, anti-inflammatory activities against four compounds, 9 R-1, S-1, 2, and R-3, were evaluated by carrageenan-induced mouse foot-pad swelling assay 10,11 at a dose of 150 mg/kg and statistical analyses were performed by Dunnett's method. Obtained data on the percentage inhibition and judgments on significant differences from the control group are summarized in Table 1.…”
mentioning
confidence: 99%
“…We evaluated six compounds (R-4 -R-9) 9 for anti-inflammatory activities by carrageenan-induced mouse foot-pad swelling assay 10,11 with a usual dose of 150 mg/kg. The percentage inhibition, determinations of S or NS, and log P values 12 of aromatic ring moiety are listed in Table 2.…”
mentioning
confidence: 99%